Concept And Implementation of Scientific Approach - Dwi Retnowati (Universitas Sebelas Maret, 2020)
There are several new things in the development and implementation of the 2013 Curriculum, one of which is the emphasis on the application of a scientific approach. The scientific approach in the 2013 curriculum emphasizes that students are actively able to construct concepts, laws or principles through several stages. The stages include five core activities which are often referred to as the 5 M, namely: observing, asking questions, gathering information, reasoning or associating, and communicating.